Predictor of Mortality COVID-19 in Two Referral Hospital in Surabaya, Indonesia - Usman Hadi; Bramanton; Tri Pudy Asmarawati; Musofa Rusli; Nasronudin; Brian Eka Rachman; M. Vitanata Arfijanto (Institute of Medico-legal Publications Pvt Ltd, 2022)
Introduction: World Health Organization had identified COVID-19 in January 2019. This disease is caused by SARS-CoV-2, which spread throughout the world and became a pandemic on March 20, 2020. COVID-19 is still a health problem because it has not clear whether the patients will be cured and survive from the disease or not. This study aims to determine the predictors of mortality from COVID-19 at Dr. Soetomo General Academic Hospital and Universitas Airlangga Hospital in Surabaya, Indonesia.Method: This study was conducted in Dr. Soetomo General Academic Hospital (referral hospital for COVID-19, 1500 beds) and Universitas Airlangga Hospital (Referal Hospital for COVID-19, 600 beds). The study used data on patients with confirmed COVID-19 who were hospitalized at these two referral hospitals. Predictors of mortality were analyzed using logistic regressions.Result: There were 247 COVID-19 patients enrolled in this study, all patients were tested positive PCR SARS-CoV-2. The main complaints were cough, nasal congestion, dyspnea, and fever. Significant predictor mortality in this study were age >60 years old (OR: 3.24, 95% CI, 1.36 - 7.70), chronic kidney disease (OR: 5.71, 95% CI, 2.05 - 15.89), obesity (OR: 8.22, 95% CI,1.5 - 54.17), malignancy (OR: 6.025, 95% CI, 1.1- 33.00), coronary heart disease (OR: 5.31, 95% CI, 1.28 - 21.98) , and C-reactive protein >10 mg/L (OR 4.603, 95% CI, 2.03 - 10.44).Conclusions: Obesity and the presence of malignancy, chronic kidney disease, heart disease and age >60 yearsold are the strongest predictors of mortality in people with COVID-19, despite high CRP results.